Housing And Services For The Elderly: A Case Study In Jinhua Street Neighborhood In Guangzhou China - Lin, Lin (Journal of Regional and City Planning, 1996)
This paper is the result of a research focuses on the elderly living in Jinhua Street in the city of Guangzhou, China. These elderly people are retirees who are women over 55 and men over 60 year of age. The paper will respond to some of the varied needs of the elderly. It is mainly concerned with the housing and services for the elder in the neighborhoods. China has the largest elderly population in the world which account for more than one—fifth of the total world elderly population. The growth speed of China’s elderly population is the fastest in the world. It took over 100 years for the western developed countries to increase its elderly population from 5% to 7%. In Japan, this process took 50 years. However, it took only about 1O years in China. The aging neighborhoods can also be found in other large cities of China, such as Beijing, Shanghai and Wuhan. This paper, therefore will be a valuable information for the renewal of the old neighborhoods and the development of new ones in china.